Complications and timing of soft tissue coverage after complete articular, open tibial plateau fractures. Issue 2 (February 2023) - Grisdela, Phillip; Olson, Jeffrey; Guild, Theodore; Dekhne, Mihir; Hresko, Andrew; Singh, Upender M.; Weaver, Michael J.; von Keudell, Arvind; Stenquist, Derek
Highlights: Open bicondylar tibial plateau fractures have a high rate of complications with a high incidence of Gustilo-Anderson type IIIB and C injuries. Time to flap coverage greater than 7 days was associated with higher rates of deep infection and unplanned reoperation in this cohort. Complication rates did not differ significantly after acute ORIF compared to staged management in the appropriately selected fracture. Abstract: Purpose: Complete articular tibial plateau fractures are typically high-energy injuries associated with significant soft tissue trauma. The primary aim of this study was to evaluate the incidence of wound complications and need for soft tissue coverage after open, complete articular tibial plateau fractures. The secondary aim was to study the effect of timing of fixation and timing of flap coverage on deep infection rates in these injuries. Methods: This was a retrospective cohort study of consecutive patients > 18 years undergoing ORIF of a Bicondylar Tibial Plateau (BTP) fracture between 2001 and 2018. Surgical data were recorded for open fractures including number of debridements, timing of definitive ORIF and soft tissue coverage relative to injury. Primary outcomes included rates of deep infection and unplanned reoperation. Results: 508 AO/OTA 41C BTP fractures were identified, with 51 open fractures included in 50 patients with a mean (SD) age 45.7 (12.3) years and a mean (SD) follow up of 4.3 (3.8) years. There were 20 cases of deep infection, unplanned reoperation occurred in 26 cases. The majority of cases (28 fractures) had initial external fixation placed, while 24 had ORIF at the initial debridement. Twelve patients had a planned flap for definitive closure on average of 6.4 days (SD 3.9) after injury, 14 required a flap for wound complications. Among patients with IIB and C injuries, rates of deep infection (5/6 vs 1/6, p = 0.02) and reoperation (5/7 vs 2/6, p = 0.08) were higher in patients treated with flap coverage >7 days from injury compared to early flap coverage. There were no differences in complication rates between early (<24hrs) and delayed fixation. Conclusions: Complete articular, open tibial plateau fractures are associated with high rates of complications. Time to flap coverage of seven days or more was a significant predictor of deep infection and unplanned reoperation in this cohort. Patients should be counseled about the high rate of unplanned reoperation and definitive soft tissue coverage should be accomplished within a week of injury whenever possible.